Simultaneous pH and EC control in hydroponics through real-time manipulation of the ammonium-to-nitrate ratio in the nutrient solution - Nicol, Willem (University of Pretoria, 2024)
Dissertation (MEng (Chemical Engineering))--University of Pretoria, 2024.